The DFT study on the electronic structure of boronic acid derivatives and its esters with fructose - Kur, Katarzyna; Kowalska-Baron, Agnieszka; Miller, Ewa (Biotechnology and Food Science, 2018)
Theoretical investigations are carried out to examine the geometrical structure and parameters of electron transitions to the lowest excited states of two boronic acid derivatives: 3-aminophenylboronic acid and 3-(acetamidomethyl)phenyl boronic acid and its cycling esters with fructose, using the DFT based 6-31 G(d,p) method. The most stable ester isomer of each acid has been selected. Predicted excitation wavelength are shorter (less than 0.5 eV) than experimental ones, what is in a good agreement considering limitations of the DFT method. In case of almost every calculated molecule the analysis of electronic transitions shows that transition S0→S1 involves electron transfer mainly from the HOMO to LUMO orbital.